Kearifan Lokal dalam Tradisi Belis pada Suku Terolau-Lau: Kajian Nilai-Nilai Budaya di Desa Kamanasa Kecamatan Malaka Tengah Kabupaten Malaka - Selestina Da costa; Clotilde Seran; Yohanis Kristianus Tampani; Antonius Bere (Jurnal Pendidikan Dirgantara, 2025)
This study examines the cultural values embedded in the Belis tradition in Kamanasa Village, Central Malaka District, Malaka Regency. The background of this research lies in the diversity of Belis practices in East Nusa Tenggara, particularly among rural communities such as the Terolau-Lau tribe, which adheres to a patrilineal system. The Belis tradition is considered significant because it reflects strong customary values and remains an obligatory practice. This study aims to describe the processes and stages of Belis implementation, identify the local wisdom values contained within it, and explain efforts to preserve this tradition amid social change. A qualitative research method was employed, with data collected through observation, interviews, and documentation. The results show that the Belis ceremony of the Terolau-Lau tribe consists of four main stages: (a) conese mentu (introduction), (b) tama husu (proposal), (c) troka prenda (engagement), and (d) lori oan feto bah mane foun nia uma lisan (the handing over of the bride to the groom’s traditional house). This tradition embodies respect for kinship, responsibility, and customary blessings as symbols of uniting two families. The community of Kamanasa Village is encouraged to maintain and uphold the local wisdom values contained in the Belis tradition.